Privatising Prisons: An endeavour for efficiency or a misinterpretation of priorities? - Constantinou, Anthony (2019)
This essay looks at the meaning of New Public Management, its history in both economic theory and political ascension and challenges its efficacy in relation to the prison service. New Public Management’s mix of new institutional economics and managerialism brought forward a wealth of claims that this new managerial practice would supersede and improve the previous traditional public administration that had been in place. The public sector as it was in the 1980s was weighing very heavy on the state and a refreshed and assertive Conservative government allowed for a stronger push to fulfil its overall objectives. This body of work uses case study methodology from the perspective of two instrumental cases to assess what has happened to New Public Management as it has been implemented into the private sector without much due care at all. The focus has been on excessively expanding competition by contracting out and market testing along with the aggressive ascension of many PFI prisons in the UK. The data collated points to the fact that this new alternative style of management that was allegedly superior to that of the traditional approach, has failed to consider the intangible underlying concepts and values that hold up the prison system and our criminal justice system as a whole. This essay looks to explain why business and punishment do not coalesce.